2020
DOI: 10.1002/mgg3.1181
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of intermediate CAG alleles of the HTT in the general population of Rio de Janeiro, Brazil, in comparison with a sample of Huntington disease‐affected families

Abstract: Background: Huntington disease (HD) (MIM: 143100) is a severe autosomal dominant neurodegenerative disease caused by the expansion of CAG trinucleotides (>35) in the HTT. Objective: To investigate the frequency of intermediate CAG alleles (IAs) in individuals residing in Rio de Janeiro city with no familial history of HD (general population, GP) in comparison with a sample of individuals from families presenting with HD who were previously investigated by our group (affected sample, AS).Results: The frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…This finding is consistent with the population studied [15]. In 2020, a study of the CAG intermediate HTT alleles in the general population of Rio de Janeiro, Brazil, compared with a sample of families affected by HD, showed that CCG7 was the most frequent allele [16]. On the other hand, the haplotypic analysis of CAG and CCG was repeated in 21 Brazilian families with HD.…”
Section: Discussionsupporting
confidence: 84%
“…This finding is consistent with the population studied [15]. In 2020, a study of the CAG intermediate HTT alleles in the general population of Rio de Janeiro, Brazil, compared with a sample of families affected by HD, showed that CCG7 was the most frequent allele [16]. On the other hand, the haplotypic analysis of CAG and CCG was repeated in 21 Brazilian families with HD.…”
Section: Discussionsupporting
confidence: 84%
“…This nding is consistent with the population studied [31]. In 2020, a study of the CAG intermediate HTT alleles in the general population of Rio de Janeiro, Brazil, compared with a sample of families affected by HD, showed that CCG7 was the most frequent allele [32]. On the other hand, the haplotypic analysis of CAG and CCG was repeated in 21 Brazilian families with HD.…”
Section: Discussionsupporting
confidence: 84%
“…In our sample of 291 individuals, the number of HTT CAG repeats ranges from 12 to 51, with an average of 21.91 copies (Table 1). Following international recommendations, we derived four subgroups according to the number of HTT CAG repeats: Normal (≤ 26 copies, n = 241, 82.8%), intermediate (27)(28)(29)(30)(31)(32)(33)(34)(35) copies, n = 16, 16%), reduced penetrance (36-39 copies, n = 1, 0.3%), and full penetrance (≥ 40 copies, n = 33, 11.3%)(Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…We read with great interest the manuscript by Apolinário and colleagues (Apolinário, da Silva, Agostinho & Paiva, 2020) about the Investigation of intermediate CAG alleles of the HTT in the general population of Rio de Janeiro, and although we understand that was not the aim of the article, we would like to contribute with an interesting clinical finding, of an ongoing study of a southern Brazilian cohort, that may highlight the discussion about the importance of intermediate alleles in Huntington's disease (HD).…”
mentioning
confidence: 99%